Perlindungan Konsumen atas Kerusakan Mesin Mobil Akibat Penggantian Kaca Film - Yusha Ridlo Pambudi (University of Jember, 2016)
Often in the community, there are cases of fraud committed by business actors that are very harmful to consumers, one of which is, there is in Supreme Court Decision Number 353 K/Pdt.Sus-BPSK/2016. The consumer shall be entitled to his / her rights such as moral rights and economic rights and one of them shall be entitled to compensation from the business actor. This thesis research discusses to know the form of legal protection to the consumer on the replacement of car window film causing a damaged car engine, to know the judge's consideration in the Supreme Court Decision Number 353 K/Pdt.Sus-BPSK/2016 is following the Law Number 8 the Year 1999 on Consumer Protection. The type of research used is juridical normative (legal research) that is positive law. This research concludes that if the consumer suffers losses on the replacement of the window film of the car that causes damage, then the business actor has violated the provisions in UUPK and must compensate for the loss caused by the business that harms the consumer. KEYWORDS: Consumer Protection, Compensation, Window Film Of The Car.